2021
DOI: 10.3390/w13111562
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Managed Aquifer Recharge (MAR) for Normal Functioning of the Public Water-Supply of Zagreb, Croatia

Abstract: With its quantities of groundwater, the Zagreb aquifer is an irreplaceable water-supply resource that forms the basis of the water-supply of Zagreb, the capital and largest city of the Republic of Croatia. The depth of the Zagreb aquifer system is about 100 m at the deepest part, and the two main aquifers of the aquifer system can be separated vertically by low-permeable clay deposits. In the area of the Zagreb aquifer, there are several active and reserve public water-supply sites, the largest of which are Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Furthermore, the results show much more deviation in the isotopic signature at the DM bridge. Together with the results of in-situ measurements and previous research, where it was shown that the connection between Sava River and Zagreb aquifer system is not uniform [6,33,42,43], these results indicate that mixing between surface water and groundwater is more pronounced in the downstream part of the Zagreb aquifer. Greater aquifer depth in the downstream part, as well as the existence of TE-TO Zagreb, generates slower velocities and enables more time for infiltration of the Sava River into the Zagreb aquifer, which is consistent with the results of the previous research [6].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the results show much more deviation in the isotopic signature at the DM bridge. Together with the results of in-situ measurements and previous research, where it was shown that the connection between Sava River and Zagreb aquifer system is not uniform [6,33,42,43], these results indicate that mixing between surface water and groundwater is more pronounced in the downstream part of the Zagreb aquifer. Greater aquifer depth in the downstream part, as well as the existence of TE-TO Zagreb, generates slower velocities and enables more time for infiltration of the Sava River into the Zagreb aquifer, which is consistent with the results of the previous research [6].…”
Section: Resultssupporting
confidence: 83%
“…Although it has been found that the main boundary condition related to the recharge of the Zagreb aquifer is the Sava River, which generates recharge from 67.5% up to 83.74% depending on the area which is evaluated [6], no research was focused on the evaluation of the Sava River isotopic pattern at the entrance of the Zagreb aquifer, i.e., the inflow area, and its isotopic difference with respect to the exit of the aquifer, i.e., the outflow area. The latest hydrogeological research confirmed that the hydraulic connection between the Sava River and groundwater is complicated and not uniform [33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improved groundwater management is needed to ensure an adequate water supply to the expanding city. One of the most appropriate ways to enhance the condition of the aquifer is to use the managing aquifer recharge (MAR) technique, which is widely used for different regions [13][14][15][16][17][18]. Regional recharge studies in the Kabul aquifer have been limited to traditional approaches to groundwater and recharge exploration which only utilized drilling and geophysical methods in some small areas sporadically due to the expensive field work investigations and the regional complexity with confrontations and wars [19].…”
Section: Introductionmentioning
confidence: 99%